INCREASING GREEN MUSTARD (Brassica juncea L.) PRODUCTION THROUGH A COMBINATION OF QUAIL MANURE AND NPK FERTILIZER - Khayatul akilah; John Nefri; Nofrianil (Universitas Veteran Bangun Nusantara, 2026)
Increasing mustard greens production requires proper fertilization that supports plant growth and maintains soil quality. The intensive application of inorganic fertilizers over a long period of time has the potential to degrade soil quality; therefore, alternative fertilization methods using organic fertilizers, such as quail manure, are needed. This study aims to analyze the growth and yield response of green mustard, with treatments involving quail manure and NPK fertilizer. The field study design used a Randomized Block Design (RBD). The treatments in this study were: no quail manure + 100% NPK fertilizer (P0), no quail manure + 50% NPK fertilizer (P1), 10 tons/ha quail manure + 50% NPK fertilizer (P2), 15 tons/ha quail manure + 50% NPK fertilizer (P3), 20 tons/ha of quail manure + 50% NPK fertilizer (P4), 25 tons/ha of quail manure + 50% NPK fertilizer (P5), and 25 tons/ha of quail manure + 0% NPK fertilizer (P6). Each treatment consisted of four groups with 28 experimental units. The results of the observations indicated that the application of quail manure and NPK fertilizer had a significant effect on stem diameter, leaf length, number of leaves, root weight, plant canopy weight, and fresh plant weight. The 25 tons/ha + 0% NPK fertilizer treatment yielded the best results for leaf number and fresh plant weight, while the 25 tons/ha quail manure + 50% NPK fertilizer treatment yielded the highest results for plant canopy weight and was able to match the results obtained from the application of 100% NPK fertilizer. Keywords: Quail Manure, NPK Fertilizer, Green Mustard Greenss